2020
DOI: 10.1002/cssc.202002427
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Synergistic Effect between Graphitic Carbon Nitride and Cu2O toward CO2Electroreduction to C2H4

Abstract: Electrochemically reducing carbon dioxide (CO2RR) to ethylene is one of the most promising strategies to reduce carbon dioxide emissions and simultaneously produce high value‐added chemicals. However, the lack of catalysts with excellent activity and stability limits the large‐scale application of this technology. In this work, a graphitic carbon nitride (g‐C3N4)‐supported Cu2O composite was fabricated, which exhibited a 32.2 % faradaic efficiency of C2H4 with a partial current density of −4.3 mA cm−2 at −1.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Great efforts have been devoted to the development of electrocatalysts for improving C 2 H 4 production from CO 2 RR, including crystal plane adjustment, [4,5] defect engineering, [6] alloying, [7][8][9] valence regulation [10] and surface molecule modification. [11][12][13] Among the cathode metals applied, Cu has been the predominant electrocatalytic material. At present, the highest Faradaic efficiency (FE) of C 2 H 4 is 87 % at À 0.47 V versus the reversible hydrogen electrode (vs. RHE), which was achieved by a Cu-polyamine hybrid catalyst conducting in a flow reactor, with a gas diffusion layer as cathode.…”
mentioning
confidence: 99%
“…Great efforts have been devoted to the development of electrocatalysts for improving C 2 H 4 production from CO 2 RR, including crystal plane adjustment, [4,5] defect engineering, [6] alloying, [7][8][9] valence regulation [10] and surface molecule modification. [11][12][13] Among the cathode metals applied, Cu has been the predominant electrocatalytic material. At present, the highest Faradaic efficiency (FE) of C 2 H 4 is 87 % at À 0.47 V versus the reversible hydrogen electrode (vs. RHE), which was achieved by a Cu-polyamine hybrid catalyst conducting in a flow reactor, with a gas diffusion layer as cathode.…”
mentioning
confidence: 99%
“…[10,11] In order to improve the selectivity of C 2 products, promoting CC coupling on the interface of Cu-based material is an effective strategy to promote the ratedetermining step of *CO dimerization to C 2 products. [12][13][14] A series of strategies such as adjusting the crystal surface structure, [15][16][17][18] generating structural defects and vacancies, [19] adjusting the relationship with the carrier, [20][21][22] and doping [23,24] have been widely reported. However, it is seldom exploited to obtain higher catalytic selectivity by adjusting the electron transport behavior at the interface of Cu-based catalysts, which is also a step that cannot be ignored during the catalytic process.…”
mentioning
confidence: 99%
“…We proposed that the high activity and high selectivity of the Cu x O/CN‐10 heterostructured catalyst originate from the interactions between Cu x O and the CN film. Many articles have also proved this assumption through DFT calculations and experiments [28,47,49] . Furthermore, we used a simple and cost‐effective preparation method to synthesize a series of Cu x O/CN catalysts and accurately control the thickness of the CN film covering the Cu x O active sites.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, two additional CO 2 ‐desorption peaks at 349 and 432 °C were observed on Cu x O/CN‐10, indicating the existence of metal‐oxygen pairs (Cu−O) [46] . The higher‐temperature CO 2 ‐desorption peaks demonstrated that the CN film increased the charge density of Cu x O active sites, and improved the chemisorption ability of CO 2 [47] …”
Section: Resultsmentioning
confidence: 96%